Meningkatkan Kemampuan Berbicara Anak Usia 4-5 Tahun Kelompok A Melalui Media Kartu Bergambar - Itasari Itasari; Nasaruddin Nasaruddin; Erwin Nurdiansyah (Ihya Ulum: Early Childhood Education Journal, 2025)
This study aims to analyze the implementation process and prove the effectiveness of improving the speaking skills of children aged 4–5 years in Group A at TK Islam Al-Fath Makassar through the utilization of flashcard media (picture cards). The background of the problem is based on initial observations indicating low ability to respond to teachers' verbal stimulation, minimal two-way communication, limited vocabulary, and weak oral articulation among children due to conventional and monotonous language learning models. The approach used is Classroom Action Research (CAR) following the Kemmis and McTaggart adaptive spiral model, conducted in two cycles, where each cycle includes the stages of planning, action, observation, and reflection. The research subjects involved 15 preschool children (7 boys and 8 girls). Data were collected through a combination of structured observation techniques and performance assessments, which were then analyzed using quantitative descriptive statistics and the interactive model of qualitative analysis. The results of the intervention demonstrate a significant acceleration in the children's expressive language competency achievement. At the end of Cycle I, the class's average oral ability score only reached 2.02 (Starting to Develop category) due to the dominance of one-way classical instruction. However, after implementing tactical reconstruction based on Developmentally Appropriate Practice (DAP) principles in Cycle II, the average class speaking skill score jumped drastically to 3.72 (Developing Very Well category). Performance improvements were consistently recorded in the aspects of fluency, vocabulary expansion, logical sentence structure composition, and the children's confidence and courage. The study concludes that the interactive-participatory operationalization of flashcards is highly effective in boosting early childhood speaking skills.